Academic Boredom in Technology-Based Mathematics Learning: A Phenomenological Study from a Didactical Mathematics Perspective - Syahrina Anisa Pulungan; Agus Maman Abadi (MASI Mandiri Edukasi, 2026)
Recent studies have shown that academic boredom negatively affects students’ engagement, motivation, and achievement; however, little is known about how students experience boredom in technology-based mathematics learning from a didactical perspective. This study aimed to explore students’ lived experiences of academic boredom, identify contributing factors, and interpret these experiences through a mathematics didactical lens. A qualitative design employing Interpretative Phenomenological Analysis (IPA) was used. Thirty-five students aged 13–15 years with experience in technology-supported mathematics learning were purposively selected to capture diverse experiences while maintaining in-depth individual and cross-case analysis. Data were collected through semi-structured interviews, classroom observations, reflective notes, and supporting documents. The findings revealed five interconnected themes: emotional exhaustion, passive engagement, monotonous learning experiences, didactical factors that fuel boredom, and students’ expectations for meaningful learning. Academic boredom emerged not only from individual emotional responses but also from repetitive instructional practices, limited interaction, weak didactical engagement, and ineffective use of educational technology. The study extends current understanding of academic boredom by demonstrating that boredom in technology-based mathematics learning is both an emotional and a didactical phenomenon shaped by instructional design and classroom interactions. These findings provide implications for developing more interactive, emotionally responsive, and meaningful mathematics learning environments.